Factors influencing the effectiveness of group interactions among international and interdisciplinary early‑career researchers working toward environmental sustainability in climate change - Enriquez, Andrea Soledad; Temoltzin Loranca, Yunuén; LLanos, Eduardo; Schrapffer, Anthony; Jansen, Sarah; Adade Williams, Portia; Saravia Tomasina, Celmira; Perez, Natalia Jesica; Kuperman, Marcelo Nestor (Springer, 2023)
Global warming is a current problem that needs to be addressed by collaborating with researchers from different disciplines and expertise. There is a concern about training the next generation of scientists to holistically address climate change. One way to address this concern is gathering researchers to promote collaboration, as a critical aspect of the scientific perspective. This study focused on the interactions among 119 early career researchers from different disciplines and countries attending the São Paulo School of Advanced Science on Climate Change 2017 in Brazil. The aim of this research case study was to identify factors and social dynamics influencing the effective generation of collaborative networks. First, social perceptions were assessed to expose factors influencing the open exchange of knowledge and dynamics among the new researchers. Second, the occurrence of interdisciplinary and intercultural interactions was evaluated using social network analysis. Using the qualitative and quantitative outcomes, perceived indicators related to barriers (e.g., language and background) and drivers (e.g., gender and age) were linked to the structure of two social networks analyzed: workplace/studyplace, and professions. Social network analysis showed that although the participants aggregated challenging the goal of collaborative networks, they actively sought interdisciplinary approaches. Based on detected barriers, future events organizers searching for an interdisciplinary climate change approach are encouraged to actively overcome these limitations by taking into account the culture, beliefs, and conceptualization aspects at a group level without overlooking individual preferences.